Uninformed Attacks on Public Education Have Increased - Weis, W. (Allies for Education, 2017)
For decades politicians have disparaged public education for stagnant or slow achievement test score growth. Public education has been called a broken system that is failing our children and our future as a nation. These increasingly misguided attacks are due to a lack of knowledge. Unfortunately, these uninformed opinions have resulted in policies that harm, rather than help students learn. This article confronts these opinions about education and sheds light on the facts.